2020
DOI: 10.29173/css2
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and Implicit Social Studies: Exploring the Integration of Social Studies Experiences in Two Elementary Classrooms

Abstract: This study explores how two elementary teachers (first and fifth grades) integrated social studies content and skills throughout their school day. More specifically, we describe and explain their social studies instruction in terms of integration as it reflects fractured, healthy, and stealthy integration (Hinde, 2015). As researchers, we spent time in two classrooms documenting the explicit and implicit social studies instruction and the interactions of teachers and students. We found examples of fractured, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Another possibility is that teachers with proximate stances teach social studies during the school day more often than their interviews revealed, but they lacked this awareness or failed to acknowledge this during the interview. This possibility is supported by Brugar and Whitlock’s (2020) case study of two elementary teachers who were unaware of some of their integration practices.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Another possibility is that teachers with proximate stances teach social studies during the school day more often than their interviews revealed, but they lacked this awareness or failed to acknowledge this during the interview. This possibility is supported by Brugar and Whitlock’s (2020) case study of two elementary teachers who were unaware of some of their integration practices.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the popularity of content integration in elementary schools, studies show that integration does not always lead to effective social studies teaching (Boyle-Baise et al, 2008; Brugar & Whitlock, 2020; Heafner, 2018). For example, Boyle-Baise et al (2008) conducted a case study of 13 elementary teachers and found that although teachers reported that they integrated social studies and reading, the content integration observed was “opportunistic, as happenstance, rather than systematic” (p. 233).…”
Section: Social Studies In Elementary Classroomsmentioning
confidence: 99%
See 3 more Smart Citations